Improving Virtual Machine Consolidation for Heterogeneous Cloud Computing Datacenters - Rodrigues, João Antonio Magri; Oliveira, Fabíola Martins C. de; Lobato, Renata Spolon; Spolon, Roberta; Manacero, Aleardo; Borin, Edson (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2019)
Datacenters in cloud computing systems may consist of thousands of computing nodes and communication devices, requiring virtual machine placement to optimize resources utilization. Heterogeneous environments of current datacenters have not been properly evaluated yet when the number of processing nodes and network devices is considered. This paper presents an approach to place virtual machines to minimize both the number of employed computing nodes and communication costs in heterogeneous environments. We evaluate our results against other known algorithms to show the efficiency of the proposed approach, which outperforms a state-of-the-art algorithm with a result of up to 13% better for network improvement while achieves the same number of computing nodes.